Informatics in Professional Education - Ball, Marion J.; Douglas, Judith V. (Methods of Information in Medicine, 1989)
The University of Maryland at Baltimore (UMAB) is a professional school campus, including schools of Dentistry, Law, Medicine, Nursing, Pharmacy, Graduate Studies, and Social Work and Community Planning. In late 1987, UMAB convened a Task Force on Informatics, intended to support the campus as it worked to become a Centre of Excellence for Informatics. The Task Force reviewed the current computing environment at UMAB and the individual schools. In assessing the state ofthe art in informatics, its work was supplemented by the formation of external advisory committees of national and international informaticians. Deliberations proceeded according to a methodology designed to develop factual databases and to generate consensus. The Task Force report, which is excerpted in the following paper, established a tiered taxonomy of competencies; defined the three levels; and set forth program models for the two higher levels. Special note was made of the programs in ´nursing and dental informatics newly established at UMAB. The report concluded with three recommendations, each with detailed action points identified.
Keywords: Medical Informatics; Education; Curriculum; Disciplines and Specialties